Lectotypification of Eriocaulon duthiei (Eriocaulaceae) - Tiwari, Arjun Prasad; Gavade, Sandip; Mujaffar, Shaikh (Phytotaxa, 2016)
The genus Eriocaulon Linnaeus (1753: 87) includes ca. 485 species and more than 40 infraspecific taxa distributed in tropical and subtropical regions of the world (Govaerts 2016). Ansari & Balakrishnan (2009) recorded 85 species from India; however, they do not include the species described earlier by Bole & Almeida (1986), Yadav et al. (2008) and the species reported by Myrthong et al. (1983). Recently, 12 species are described within the genus (Shimpale et al. 2009, Shimpale & Yadav 2010, Vivek et al. 2010, Nampy et al. 2011, Swapna et al.2012, Biju et al. 2012, Sunil et al. 2013, Rashmi & Krishnakumar 2014, Manudev et al.2015, Sunil & Naveen Kumar 2015, Sunil et al. 2015).